Association between the cost of dual-task and cognitive function in older people with Motoric Cognitive Risk Syndrome: a cross-sectional study. - de Amorim Batista, Gabriel; Calixtre, Letícia Bojikian; Cavalcante, Bruno Remígio; de Araújo Silva, Juliana Daniele; Sampaio Amaral, Késia Moreira; Gonçalves, Ruth Lahis da Silva; Callisaya, Michele; Rodarti Pitangui, Ana Carolina; de Araújo, Rodrigo Cappato (Journal of Physiotherapy Research / Revista Pesquisa em Fisioterapia, 2025)
BACKGROUND: Dual-task mobility tests are considered more sensitive than single-task assessments for detecting early cognitive impairment in older adults. However, their association with cognitive performance in individuals with Motoric Cognitive Risk Syndrome (MCR) has not been well established. OBJECTIVE: To investigate the relationship between the cost of dual-task testing in the Timed Up and Go (TUG) test with different cognitive demands and cognitive function in older individuals with MCR. METHODOLOGY: Fifty-nine older individuals with MCR were included (89.8% women; mean age: 70 years). The cost of dual-task testing was assessed in two conditions: TUG with counting backwards and TUG with animal naming. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA), Trail Making Test Part A (TMT-A), Digit Span, and Verbal Fluency tests. Multiple linear regressions, adjusted for age, sex, and education, were conducted. RESULTS: The dual-task cost of the TUG with counting backwards correlated positively with performance in attention and processing speed (TMT-A; r = 0.52; β = 0.17 [0.05 to 0.29]) and negatively with global cognitive performance (MoCA; r = -0.48; β = -1.18 [-2.22 to -0.11]). The TUG with animal naming showed no significant associations with cognitive tests. CONCLUSION: The dual-task cost during the TUG with counting backwards was moderately associated with attention, processing speed, and global cognition in older adults with MCR. No significant associations were observed for the TUG with animal naming. These findings highlight that the type of cognitive demand used in dual-task testing may influence the degree of motor-cognitive interference.